2017
DOI: 10.1097/id.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histomorphometrical Determination of the Biogradation of β-Tricalcium Phosphate Granules in Maxillary Sinus Floor Augmentation

Abstract: Highly pure β-TCP is a safe bone-grafting material with superior osteoconductive properties. Histologic and radiographic examinations indicate that β-TCP is slowly resorbed, which results in unresorbed graft material remaining even 6 months after the procedure, and that new bone replacement occurs slowly for approximately 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…In another study, the TCP that was grafted into the maxillary sinus was absorbed, albeit in a very slow manner; it was replaced with new bone in about 6 months to 1 year [10]. However, in the current case report, a TCP-like radio-opacity was clearly observed on the CBCT image at 1 year, and the TCP degradation process could take longer than 1 year.…”
Section: Discussioncontrasting
confidence: 48%
“…In another study, the TCP that was grafted into the maxillary sinus was absorbed, albeit in a very slow manner; it was replaced with new bone in about 6 months to 1 year [10]. However, in the current case report, a TCP-like radio-opacity was clearly observed on the CBCT image at 1 year, and the TCP degradation process could take longer than 1 year.…”
Section: Discussioncontrasting
confidence: 48%
“…Because ß‐TCP‐based compounds exhibit a better organic response either alone or in combination with osteogenic substances, along with their biocompatibility and osteoconductive potential, several studies have compared their biological behavior as a bone substitute based on scientific evidence from commercially available materials . It was shown previously that the bioactivity of these biomaterials is related to the respective amounts of HA and ß‐TCP in each compound .…”
Section: Discussionmentioning
confidence: 99%
“…According to one study on the use of BoneCeramic in the maxillary 19,25 Because ß-TCP-based compounds exhibit a better organic response either alone or in combination with osteogenic substances, along with their biocompatibility and osteoconductive potential, several studies have compared their biological behavior as a bone substitute based on scientific evidence from commercially available materials. 18,[26][27][28][29][30][31] It was shown previously that the bioactivity of these biomaterials is related to the respective amounts of HA and ß-TCP in each compound. 32 Some clinical studies have shown the advantages of alveolar filling immediately after tooth extraction for the preservation of bone architecture for subsequent implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…The β-TCP used in this study has only osteoconductive properties during absorption. Okada et al [20] reported that in maxillary sinus floor augmentation with the lateral approach, β-TCP was slowly replaced by new bone during the year after the graft was received. In this study, dome-shaped β-TCP was observed immediately after surgery, and the CBCT image decreased at follow-up.…”
Section: β-Tcp Absorption and New Bone Formationmentioning
confidence: 99%